ESTIMATION OF GENETIC DIVERSITY FOR ANAEROBIC GERMINATION TRAITS USING PRINCIPAL COMPONENT ANALYSIS IN RICE ( YSIS IN RICE (Oryza sativa Oryza sativa L.) - K. SUDEEPTHI; T. SRINIVAS; B.N.V.S.R RAVI KUMAR; JYOTHULA D.P.B; S. K. NAFEEZ UMAR (The Bioscan, 2019)
Principal component analysis was carried out to assess the diversity among 107 rice genotypes with regards to anaerobic germination traits. Results revealed two principal components with eigen value > 1. These components contributed for a total variability of 77.662 per cent. Component 1 (PC 1) had contributed maximum (57.897 %) while component 2 (PC 2) had contributed to 19.764 per cent towards the total variability. The characters, namely, germination per cent, shoot length, anaerobic response index and root length explained maximum variance in PC 1. The PCA scores for 107 genotypes were plotted in graph to get two dimensional scatter diagram. The results of 2D scatter diagram revealed maximum diversity between the genotypes number (MTU 1140) and (MTU 1010) and hybridization of these diverse genotypes is therefore predicted to result in transgressive segregants with high yield and tolerance to germination under anaerobic conditions.